Analysis Of The Contribution Of On-Grid Plts To Electricity Bill Costs - Suparman Suparman; Muhammad Natsir Rahman; Faris Syamsudin; Dhody Haudy Rumalean (PROtek : Jurnal Ilmiah Teknik Elektro, 2026)
Indonesia's electricity needs are still heavily dependent on fossil fuels, necessitating the development of more environmentally friendly alternative energy sources. One potential solution is the use of rooftop solar power plants (PLTS). This research aims to design an on-grid rooftop solar power system for the Integrated Lecture Building (SBSN) at Khairun University. The research phase involved collecting data on the building's electricity consumption, potential solar radiation at the site, and calculating the system design based on module capacity, number of panels, and performance ratio (PR). The analysis revealed that an installed capacity of 40 KWP can generate 52,560 kWh of electricity per year. Compared to the building's total annual electricity demand of 266,400 kWh, this PLTS contributes 19.7%. The economic analysis also indicates potential savings of approximately Rp 3.22 million per month or Rp 38.67 million per year in electricity costs. Therefore, the implementation of rooftop solar power plants is considered a viable renewable energy solution to reduce electricity costs while supporting the implementation of clean energy on campus.